Changes in a cerebellar peduncle lesion in a patient with Dandy-Walker malformation A diffusion tensor imaging study - Lee, Ah Young; Jang, Sung Ho; Yeo, Sang Seok; Lee, Ensil; Cho, Yun Woo; Son, Su Min (Neural regeneration research, 2013)
We report a patient with severe ataxia due to Dandy-Walker malformation, who showed functional recovery over 10 months corresponding to a change in a cerebellar peduncle lesion. A 20-month-old female patient who was diagnosed with Dandy-Walker syndrome and six age- and sex-matched healthy control subjects were enrolled. The superior cerebellar peduncle, the middle cerebellar peduncle, and the inferior cerebellar peduncle were evaluated using fractional anisotropy and the apparent diffusion coefficient. The patients＇ functional ambulation category was 0 at the initial visit, but improved to 2 at the follow-up evaluation, and Berg＇s balance scale score also improved from 0 to 7. Initial diffusion tensor tractography revealed that the inferior cerebellar peduncle was not detected, that the fractional anisotropy of the superior cerebellar peduncle and middle cerebellar peduncle decreased by two standard deviations below, and that the apparent diffusion coefficient increased by two standard deviations over normal control values. However, on follow-up diffusion tensor tractography, both inferior cerebellar peduncles could be detected, and the fractional anisotropy of superior cerebellar peduncle increased to within two standard deviations of normal controls. The functional improvement in this patient appeared to correspond to changes in these cerebellar peduncles. We believe that evaluating cerebellar peduncles using diffusion tensor imaging is useful in cases when a cerebellar peduncle lesion is suspected.